(3JGQjN Gdedhc GdYKeGfjI hGdhRQGA hGdUOhQ heTGjN GdESdGe hGdbHhOGfGJs ((3CMeO YQGHi s)
(3ChdgG (B:s
(3MeOkG dPi GdSWGf GdOGFe HdG hRQ GdN s
(3BNQgG (B:s
(3hcGf GdaQGZ ef Jfejb gPG GdJGQjN GddWja ai (B15 (3LeGOi GdBNQ SfI (B1272(3Ydi jO cGJHg GdabjQ CMeO YQGHi GdTGaYi s
(3GdfSNI HgG MhGTs
(3hgh JGQjN eNJUQ GdSdGWjf Bd YKeGf hQLGd OhdJges
(3YHGQI Yf LOGhd HJGQjN ejdGOge hhdGOJge hhaGJge Edi ChGNQ GdbQf GdKGdK YTQs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs